Agronomic interventions for a sustainable rice based cropping system in paddy fields - Vipitha V P (Department of Agronomy, College of Agriculture, 2016)
The experiment entitled “Agronomic interventions for a sustainable rice based cropping system in paddy fields” was conducted at the Instructional farm, College of Agriculture, Vellayani, Kerala during the period from 2013-14 (first year) to 2014-15 (second year) in reclaimed paddy field. The main objectives were to evaluate the impact of agronomic interventions on growth, productivity and sustainability of a rice based cropping system and to study the nutrient balance, energetics and economics of the cropping system. The sequential cropping system consisted of rice (first crop) succeeded by cassava intercropped with groundnut (second crop) and cowpea (third crop). The experiment was laid out in split plot design with five replications. The treatment comprising three main plots were assigned with methods of planting in combination with weed control measures viz: M1- broadcasting of sprouted seeds, M2- dibbling (sprouted seeds with drum seeder along with weeding by power weeder) and M3- dibbling (sprouted seeds with drum seeder along with stubble mulching). Five methods of fertilizer application constituted the sub plot treatments [F1- broadcasting (60:30:30 kg NPK ha-1 at 10 DAS, tillering and panicle initiation stage), F2- band placement (60:30:30 kg NPK ha-1 at 10 DAS, tillering and panicle initiation stage), F3- foliar spray of water soluble complex fertilizer 19:19:19 @ 0.5 per cent (at tillering, panicle initiation and flowering stage), F4- foliar spray of diammonium phosphate (DAP) and sulphate of potash (SOP) each @ 2 per cent (at tillering, panicle initiation and flowering stage), F5- control] for upland rice. Farmyard manure @ 5 t ha-1 was applied uniformly to all the treatments except control. For cassava intercropped with groundnut and cowpea, recommended dose of fertilizers (FYM @ 12.5 t ha-1, 110:120:120 kg NPK ha-1 for cassava+groundnut and FYM @ 20 t ha-1, 20:30:10 kg NPK ha-1 for cowpea) along with 0.5 per cent foliar spray of water soluble complex fertilizer 19:19:19 was applied at 30 (up to three weeks before harvest in both cassava and groundnut) and 14 days (up to one week before first harvest in cowpea) interval. The varieties used for the study were Aiswarya (rice), Vellayani Hraswa (cassava), TMV-2 (groundnut) and Bhagyalakshmi (cowpea). The same experiment was repeated in the second year for confirmatory results. The results indicated that methods of planting and weed control measures along with methods of fertilizer application had significant effect on the yield attributes and yield of first crop, rice. During first year among the main plot treatments, the highest grain yield was produced in M2 (dibbling of sprouted seeds +power weeding) and it was on par with M3 (dibbling of sprouted seeds + stubble mulching). The subplot treatments were not significant. The treatment m2f2 (dibbling of sprouted seeds + power weeding along with band placement of 60:30:30 kg NPK ha-1) produced the highest number of productive tillers m-2, number of grains panicle-1,thousand grain weight, grain yield (2927.97 kg ha-1), straw yield and B:C ratio (1.65). During second year, the main plot treatments were not significant and among the methods of fertilizer application, F3 (foliar spray of 19:19:19 @ 0.5 %) resulted in the highest grain yield and was on par with F2 and F4. Comparing the interaction, the higher yield attributes and grain yield (3109.33 kg ha-1) were produced in m2 (dibbling of sprouted seeds +power weeding) along with f3 (foliar spray of 19:19:19 @ 0.5 %) with a B:C ratio of 2.38. It was on par with m1 (broadcasting of seeds) along with f2 (band placement of 60:30:30 kg NPK ha-1) and f3 and m2 along with f2 and f4 (foliar spray of DAP and SOP each @ 2 %). For cassava intercropped with groundnut, the residual effect of stubble mulching of rice along with broadcasting of 60:30:30 kg NPK ha-1 (m3f1) produced the highest tuber yield and utilization index of cassava and the highest pod yield and kernel yield of groundnut in the first year. The treatment combination of m3f1 was on par with m1f1 [residual effect of broadcasting of seeds (m1) along with broadcasting of 60:30:30 kg NPK ha-1 (f1)] (tuber yield) in cassava and it was on par with m1 along with f5 (control) and m3 along with f3 (residual effect of foliar spray of 19:19:19 @ 0.5 %) (pod yield and kernel yield) in groundnut. During second year, m3f1 produced the highest yield and yield attributes and it was on par with m3f4 (residual effect of stubble mulching of the first crop rice along with foliar spray of DAP and SOP each @ 2 %) in cassava. The combination of m3f4 produced the highest yield and yield attributes in groundnut which was on par with m1f4.